2021
DOI: 10.1007/978-3-030-86800-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Playing (Government) Seriously: Design Principles for e-Government Simulation Game Platforms

Abstract: The digital transformation of the public sector is progressing but regularly not at the desired pace. Here, the digitalization skills of public officials are one important resource to cope with the demanding digital shift and rise of egovernment. As there is still a lack of those competences, alternative educational approaches are needed. Promising and flexible methods are simulation gamesalthough not widely used in the public sector. As a resolve, we are developing on a corresponding simulation game platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This shift towards digitization in the public sector has enabled a more citizen-centric approach to service delivery. It has improved efficiency by implementing digital services and reorganizing workflows [7].…”
Section: Introductionmentioning
confidence: 99%
“…This shift towards digitization in the public sector has enabled a more citizen-centric approach to service delivery. It has improved efficiency by implementing digital services and reorganizing workflows [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that simulation games have a behavioral change effect on the people who play them [12] [13]. Simulation games can be a medium to convey complex concepts so that they are more easily accepted [14] [15]. The simulation game is built with a Single Page Application (SPA) approach.…”
Section: Introductionmentioning
confidence: 99%